Comparative study of effects of natural organic additives and cellulose ether on properties of lime-clay mortars. (1st May 2022) - Hwang, Hee-Young; Kwon, Yang-Hee; Hong, Sung-Gul; Kang, Sung-Hoon
Abstract: Admixtures have long been used to improve the performance of lime-based materials. In addition to various natural organic additives, cellulose ethers are widely applied due to their ease of use and reasonable price. In this study, three natural organic additives traditionally used in East Asia (starch, sticky rice, and seaweed pastes) and one type of cellulose ether, specifically hydroxypropyl methylcellulose (HPMC), were compared with respect to their effects on the properties of lime-clay mortar. HPMC and seaweed paste substantially increased the mortar strength by 2.22 and 3.59 times, respectively, whereas starch and sticky rice pastes slightly increased the strength by 1.04 and 1.31 times, respectively. The mechanism of strength improvement can be explained by the type of admixture. HPMC, starch, and sticky rice induce the formation of small calcium carbonate crystals, beneficial for pore refinement due to slow carbonation. Particularly, the remarkable strength enhancement by the cellulose ether is attributed to the fiber-bridging action by cellulose molecules. In the case of seaweed paste, salt species (sodium chloride and sodium alginate), originating from seaweed, act as a carbonation accelerator. Seaweed paste effectively improved various performances (workability, compressive strength, and crack mitigation) of the mortar, while HPMC showed adverse effects on the rest of the performances other than strength. Highlights: The use of hydroxypropyl methylcellulose significantly (by 3.6 times) improves compressive strength of lime-clay mortars. Seaweed paste improves workability and compressive strength (by 2.2 times) of the mortars. The viscous characteristic of seaweed paste contributes to improving water retention and crack mitigation the mortars. The salt in seaweed acts as a carbonation accelerator.